Insights into the Quorum Sensing Regulon of the Acidophilic Acidithiobacillus ferrooxidans Revealed by Transcriptomic in the Presence of an Acyl Homoserine Lactone Superagonist Analog - Mamani, Sigde; Moinier, Danielle; Denis, Yann; Soulère, Laurent; Queneau, Yves; Talla, Emmanuel; Bonnefoy, Violaine; Guiliani, Nicolas (Frontiers in Microbiology, 2016)
While a functional quorum sensing system has been identified in the acidophilic chemolithoautotroph Acidithiobacillus ferrooxidans ATCC 23270T and shown to modulate cell adhesion to solid substrates, nothing is known about the genes it regulates. To address the question of how quorum sensing controls biofilm formation in At. ferrooxidansT, the transcriptome of this organism in conditions in which quorum sensing response is stimulated by a synthetic superagonist AHL analogue has been studied. First, the effect on biofilm formation of a synthetic AHL tetrazolic analogue, tetrazole 9c, known for its agonistic QS activity, was assessed by fluorescence and electron microscopy experiments. A faster adherence of At. ferrooxidansT cells on sulfur coupons was observed. Then, tetrazole 9c was used in DNA microarray experiments that allowed the identification of genes regulated by quorum sensing signalling, and more particularly, those involved in early biofilm formation. Interestingly, afeI gene, encoding the AHL synthase, but not the At. ferrooxidans quorum sensing transcriptional regulator AfeR encoding gene, was shown to be regulated by quorum sensing. Data indicated that QS network represents at least 4.5 % (141 genes) of the ATCC 23270T genome of which 42.5 % (60 genes) are related to biofilm formation. Finally, AfeR was shown to bind specifically to the regulatory region of the afeI gene at the level of the palindromic sequence predicted to be the AfeR binding site. Our results give new insights on the response of At. ferrooxidans to quorum sensing and on biofilm biogenesis, opening new biological/chemical alternatives for bioleaching development and managing acid Mine/Rock drainage environmental damages.